The Issue Of Safeguarding The Craftsmanship In Penang : A Case Study Of Penang Heritage Trust (Pht) - Balakrishnan, Preveena (2014)
This case study is about the research to identify the problem faced in safeguarding the traditional crafts in the penang which is classified under the craftsmanship domain for the unesco classification of the intangible cultural heritage. This case study has chosen penang heritage trust a non-govemment organization (ngo) which is running the penang apprenticeship programme for artisans (papa). This programme is managed with the interest to protect the traditional craft which is considered to be one of the unesco intangible cultural heritage domains. The issue pertaining to this programme is where the income generated from this programme has decreased in time and the low enrolment from the younger generation for this programme due to the several factors. This study was under taken to identify the factors that have contributed to challenges faced by in sustaining the programme as well to income generation. The method used to analyse the root cause are fish bone analysis and pareto analysis. Several suggestions with best known model are suggested in to order to enhance the performance based on the findings.